Agents and artificial intelligence : 9th International Conference, ICAART 2017, Porto, Portugal, February 24-26, 2017, Revised selected papers /: 9th International Conference, ICAART 2017, Porto, Portugal, February 24-26, 2017, Revised selected papers. (2018) - Unknown
No abstract available